Idiopathic epilepsy with generalized tonic clonic seizures in Antioquia, Colombia: Is the joint Amerindian and Negroid racial admixture the cause of its high prevalence? (1996)
ABSTRACT: Most Colombian populations stem from the admixture of Caucasians, Amerindians and Negroids. In the world, these two latter ethnical groups show a significantly higher prevalence of epilepsy than the former one. We tested the hypothesis that the high prevalence of idiopathic epilepsy with generalized tonic clonic seizures found in the Antioquian population (Paisas), from Colombia, is due to their possible joint Negroid and Amerindian ethnic components. We have previously demonstrated that inheritance is the principal factor for developing epilepsy in this community. Analyses of racial admixture, heterogeneity between populations, genetic distance, and phyletic relationships were performed among epileptic and non epileptic samples from the Antioquian community. Also Caucasians, Spaniards, Basques, Jews, Chileans, Negroids, Amerindians and Mongoloids were included in the analysis. Four highly polymorphic blood systems were used as genetic markers: RH, MNS, ABO and FY. They were chosen because of their high discriminant power in these ethnic groups. In the population affected with idiopathic epilepsy, the estimated Negroid and Amerindian rates of admixture were low (3% and 14%, respectively). Although, these degrees of admixture can be explained due to common ancestral origins, the estimated proportion of Amerindian admixture in the epileptic affected population, was significantly higher than the estimated for the Non affected Antioquian population. The latter finding is consistent with the analysis of heterogeneity between populations that discriminated epileptic population from non epileptic Antioquian population (p<0.05). Epileptic and non epileptic Paisas clustered in topology with Caucasians, very close to Spaniards and Basques and highly distant from Negroids and Amerindians. Thus far, the origin of the high prevalence of idiopathic epilepsy in the Antioquian (Paisa) population cannot be explained by the hypothetical joint Negroid and Amerindian ethnical admixture, but using additional genetic markers and other methods of racial estimation of admixture it is necessary to corroborate if the Amerindian admixture component is significantly higher in the epileptic population than in the non epileptic Paisa population.